Interlocking nailing in fractures of distal tibia - Phadke, Akshay; Badole, Chandrashekhar; Thakur, Shailendra; Handa, Kriti (International Journal of Research in Medical Sciences, 2016)
Background: The complex biomechanics of distal tibial fractures, lack of robust soft tissue coverage and a wide metaphysis makes their treatment a challenging prospect even for experienced surgeons. Methods: A total of 42 patients of distal tibia fracture were treated with reamed intramedullary nailing. Fibula was fixed in selected cases either with nailing or a low profile plate. Outcome was measured with Klemm and Borner criteria. Results: In this study 42 patients treated with reamed IM nailing were included. Fractures were classified according to AO classification. In present study, we got 22 patients (53.38 %) of fracture 43A1, 11 patients (26.19%) 43A2 and 9 patients (21.42%) 43A3 type. Fibular fracture was fixed with plate in 16 patients and intramedullary device in 15 patients. In the study all the fractures united. Mean time for union was 21 weeks. Time range for union was from 12-34 weeks. Four patients had mal-alignment. One patient had superficial infection which was treated with oral antibiotics. In the present study, 35 (83.33%) patients had no loss of ankle motion, while 5 (11.90 %) had loss of <25 degrees and 2 had loss of 25 degrees. Out of 42 patients, 33 (78.58%) patients had excellent results while 5 (11.90%) patients had good results, 4 (9.52%) patients had fair results. Conclusions: Intramedullary nailing is an effective alternative for the treatment of distal metaphyseal tibial fractures. A proper patient selection, adjuvant fixation of fibula and use of at least two distal interlocking screws is suggested for better outcome.